2015
DOI: 10.1111/nep.12363
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous measurement of glomerular filtration rate in small rodents: Through the skin for the win?

Abstract: This methods in renal research article describes a new non-invasive technique to measure glomerular filtration rate in small animals. Furthermore, this technology has potential for broader use in renal research, such as in measuring the rate of clearance of albumin from the circulation in animals with proteinuria. ABSTRACT:Rodent models of renal physiology and pathology are crucial to our understanding of the molecular, histological and functional sequelae that contribute to kidney diseases. One of the most im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…a progressive decline in GFR. Previous studies have demonstrated the accuracy and reliability of the transcutaneous measurement of FITC-sinistrin half-life as a measure of GFR in various strains of rats and mice 10 11 18 20 21 22 23 . Of note, although remaining elevated, the degree of albuminuria fell between weeks 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…a progressive decline in GFR. Previous studies have demonstrated the accuracy and reliability of the transcutaneous measurement of FITC-sinistrin half-life as a measure of GFR in various strains of rats and mice 10 11 18 20 21 22 23 . Of note, although remaining elevated, the degree of albuminuria fell between weeks 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…GFR was measured in 14-week-old HbSS and HbAA mice (1 day before metabolic cage studies) using transcutaneous measurement of fluorescein isothiocyanate-labeled sinestrin technique as previously described. 64…”
Section: Gfr Measurementsmentioning
confidence: 99%
“…On the day of GFR measurement, spiny mice were briefly (~5 min) anaesthetized (isoflurane), the photodiode recording device (NIC-Kidney Device) secured to the exposed skin with double-sided adhesive tape before giving an intracardiac injection of FITC-sinistrin (1.5 μl/g body weight of 35 mg/ml sinistrin in 0.9% NaCl; total volume 30-45 μl). Spiny mice were returned to their home cage and the elimination kinetics (halftime, t 1/2 ) recorded for the next 1 h (22).…”
Section: Transcutaneous Measurement Of Fitc-sinistrin Clearancementioning
confidence: 99%